2001
DOI: 10.1038/nn728
|View full text |Cite
|
Sign up to set email alerts
|

Lateral interactions between targets and flankers in low-level vision depend on attention to the flankers

Abstract: Detection of an oriented visual target can be facilitated by collinear visual flankers. Such lateral interactions are thought to reflect integrative processes in low-level vision. In past studies, the flankers were task-irrelevant, and were typically assumed to be unattended. Here we manipulated attention to the flankers directly, by requiring observers to judge the relative alignment of two flankers while ignoring a second flanker-pair. Under identical stimulus conditions, attended flankers produced typical l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
133
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(148 citation statements)
references
References 31 publications
12
133
3
Order By: Relevance
“…1c, the two relevant central bars had the same orientation and the effect of cueing on the representation of the irrelevant bars cannot be explained by feature-based attention. A previous study 14 showed that a chain of taskrelevant collinear bars induces attentional modulation in V1 whereas the present results show that attention spreads from attended bars to nearby irrelevant bars, but only if they are collinear 15 . The present and previous results, taken together, suggest a common framework for the effects of collinearity and feature similarity.…”
Section: Paired T-test)contrasting
confidence: 78%
“…1c, the two relevant central bars had the same orientation and the effect of cueing on the representation of the irrelevant bars cannot be explained by feature-based attention. A previous study 14 showed that a chain of taskrelevant collinear bars induces attentional modulation in V1 whereas the present results show that attention spreads from attended bars to nearby irrelevant bars, but only if they are collinear 15 . The present and previous results, taken together, suggest a common framework for the effects of collinearity and feature similarity.…”
Section: Paired T-test)contrasting
confidence: 78%
“…Finally, a fresh replication of the original Freeman et al (2001) design with non-rotated single-axis (figures 1a and 1b) and dual-axis stimuli (figures 1c and 1d) was also included, to allow within-subjects comparisons against the novel conditions introduced in this experiment.…”
Section: Methodsmentioning
confidence: 99%
“…We recently reported psychophysical data suggesting that lateral interactions between a target and collinear flankers might be modified by top^down attention (Freeman et al 2001(Freeman et al , 2003. We used displays that comprised four suprathreshold flankers (figures 1c and 1d) surrounding a central near-threshold target (ie two pairs of flankers, rather than the usual single pair; see figures 1a and 1b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local context influences the ability to detect or discriminate visual targets (Ito et al 1998;Ito and Gilbert 1999;Zenger et al 2000;Freeman et al 2001;Albright and Stoner 2002;Schwartz et al 2007;Thiele 2007). Certain contextual configurations result in pop-out which enhance stimulus detection (Nothdurft 1993;Wang et al 1994;Braun and Julesz 1998), while others result in crowding and impair stimulus detection (Pelli et al 2004).…”
Section: Introductionmentioning
confidence: 99%